1995
DOI: 10.1002/aja.1002030110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of ouabain on early heart development and cardiomyogenesis in the chick embryo

Abstract: Pericardial cavity formation and epithelialization of the cardiac precursor cell population constitute a critical developmental period that precedes stable cardiac cell commitment and differentiation. These events delineate the myocardial and endocardia1 precursor population in the embryo. Restriction of NaK-ATPase (the sodium pump) expression to the pre-cardiomyocyte lateral membranes coincides with these events. NaK-ATPase has been implicated developmentally in cavitation and in maintaining membrane potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Our previously published results indicated that ouabain, an inhibitor of the sodium pump, arrested cardiac cell differentiation at a step associated with cardiac cell epithelialization (Linask and Gui, 1995). The sole function of ouabain has been shown experimentally to be an inhibition of Na-K-ATPase (sodium pump) activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previously published results indicated that ouabain, an inhibitor of the sodium pump, arrested cardiac cell differentiation at a step associated with cardiac cell epithelialization (Linask and Gui, 1995). The sole function of ouabain has been shown experimentally to be an inhibition of Na-K-ATPase (sodium pump) activity.…”
Section: Resultsmentioning
confidence: 99%
“…Ouabain exposure of whole embryos demonstrated that pericardial coelom development and cardiomyocyte differentiation were blocked principally between stages 4 to 7 in a rostrocaudad gradient. After stage 7 ϩ /8 ouabain no longer affected these cardiac developmental processes (Linask and Gui, 1995). Ouabain inhibition of cardiac cell differentiation suggested that intracellular ionic concentrations may be closely tied to early cardiac signaling and that this may involve also the sodium-calcium exchanger (NCX).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process progresses in an anterior to posterior manner across the heart fields (Linask, 2003). The signaling is accompanied by a mesenchymal to epithelial cardiac cell shape change (Linask et al, 1992(Linask et al, , 1997Linask, 1992aLinask, ,b, 2003Linask and Gui, 1995). The mesenchymal to epithelial cell transformation coincides with initiation of cardiomyocyte phenotypic differentiation, i.e., into polarized cells with initiation of myofibrillogenesis (Linask, 1992a;Linask et al, 1997;Imanaka-Yoshida et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…They were removed after a total incubation period of 30 hr and fixed overnight in 4% paraformaldehyde. The in situ hybridization was carried out as previously described (Linask and Gui, 1995). The chick probe for Dkk-1 was provided by Dr. Susan C. Chapman (University of Utah, Salt Lake City, UT).…”
Section: In Situ Hybridizationmentioning
confidence: 99%